(untitled) (Academia Science Repository, 2023)
This paper is devoted to the study the evolution and ethnic structure of the Uzbeks living in the Sangzor Oasis (modern Jizzakh region of Uzbekistan). The author tries to analyze the ethnic composition of the inhabited, local populationin of Sangzor in the late 19th – Early XX Centuries, as well as the influence of the resettled population as a result of the migration policy of the Russian Empire on the ethnic processes in the oasis in the Late 19th – Early 20th Century, according to primary sources.